1988
DOI: 10.1093/ajh/1.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Hypertension Accelerates Nephropathy in the Streptozotocin Diabetic Rat

Abstract: To evaluate whether hypertension is a cause or just an association with diabetic renal disease, diabetes was induced in both normotensive Wistar-Kyoto and spontaneously hypertensive rats (WKY and SHR). Animals were assessed monthly for 8 months before sacrifice. When compared to normotensive diabetic rats (WKY-STZ), hypertensive diabetic rats (SHR-STZ) had an earlier and more rapid rise in urinary albumin excretion. In addition, SHR-STZ had increased glomerular basement membrane thickness when compared to WKY-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 0 publications
0
36
1
3
Order By: Relevance
“…In diabetic SHR the ACE inhibitor enalapril attenuated but did not normalize progression of albuminuria. 37 In the study of Lewis and coworkers, 38 renal impairment still progressed in patients with diabetic nephropathy, especially if hypertensive, despite partial renoprotection observed in captopril-treated patients. The available data suggest that strict control of blood pressure is essential to confer the full renal and cardioprotective effects of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic SHR the ACE inhibitor enalapril attenuated but did not normalize progression of albuminuria. 37 In the study of Lewis and coworkers, 38 renal impairment still progressed in patients with diabetic nephropathy, especially if hypertensive, despite partial renoprotection observed in captopril-treated patients. The available data suggest that strict control of blood pressure is essential to confer the full renal and cardioprotective effects of antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…28 The development of diabetic renal injury was accelerated by uninephrectomy, which has been shown to increase glomerular capillary hydraulic pressure and plasma flow rate in nondiabetic rats. 29 This study confirmed that in SHR a high salt intake prevents the hypotensive effect of chronic ACE inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The functional and structural characteristics of this diabetic nephropathy model were fully described previously [17]. Indeed, Righetti et al [18] recently demonstrated an earlier accumulation of cortical renal fibronectin, a matrix protein implicated in renal glomerulosclerosis, in diabetic SHR as compared with diabetic control rats.…”
Section: Introductionmentioning
confidence: 86%